Application of Self-adapting Radar Video Echo Acquisition System based on LZW Algorithm - Liu Xin; Ren Yongfeng; Chu Chengqun (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Sampling radar video echo signal is widely known as an effective method to explore the target information in remote sensing. Large number of echoes must be acquired in real time. A typical radar acquisition system involves high-speed ADC, front-end filter and signal process module. A multi-channel adaptive variable sampling rate data acquisition system based on FPGA and I2C bus is introduced. Not only can it be used in the field of radar video echo data acquisition system but also be used to achieve normal data acquisition in industry. By writing the frame data into E2PROM and the design of interface between FPGA and E2PROM, multi-channel data programmable sampling is realized. In addition, in order to reduce the data volume in signal process module, real-time lossless compression algorithm LZW based on FPGA is proposed. It can be realized by programming in FPGA. The algorithm principle of LZW and the coding flow are introduced. By using different file types to test the compression algorithm, satisfactory results can be obtained. This lossless compression algorithm based on hardware can reduce the complexity of the signal processing to some extent. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3210